Revista Latinoamericana de Derechos humanos: 20 years - Cerdas Agüero, Evelyn (2020)
The objective of this article is to review 20 years of history of the Revista Latinoamericana de Derechos Humanos from its beginnings as DEHUIDELA in 2009.  This is achieved through a descriptive analysis based on information gathered from the reports presented annually to IDELA, from each published journal number and its website.  The article proposes that this publication is born as an effort of the Instituto de Estudios Latinoamericanos (Institute of Latin American Studies) (IDELA) to support the Human Rights Program, as well as an opportunity to develop various themes that will stimulate the students of the Institute in their research topics.  Starting with a new effort in 2009, the journal takes a step to become an indexed scientific publication whose main focus is the publication of works related to human rights as perceived from various disciplines and approaches.  It is concluded that the work input over the years has made the Revista Latinoamericana de Derechos Humanos a quality print and electronic publication that contributes to the dissemination of knowledge of human rights in Latin America from within the public university.